2014
DOI: 10.1016/j.jegh.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical fitness and weight status among fisherwomen in relation to their occupational workload

Abstract: This study implies that physical fitness and weight status of young fisherwomen in Eastern India are influenced by their occupational workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The curve regression analysis of BMI and PFI showed that there was an inverted “U” curve relationship between BMI and PFI in Tibetan children and adolescents in high-altitude areas. Our findings are consistent with the conclusions of several studies [ 9 , 14 ]. Compared with girls, the curve relationship of boys is more “steep”, which also shows that the impact of malnutrition and obesity on physical fitness of Tibetan boys is significantly higher than that of girls; especially the impact of BMI on PFI in boys in Lhasa and Nyingchi is more obvious, namely steeper.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The curve regression analysis of BMI and PFI showed that there was an inverted “U” curve relationship between BMI and PFI in Tibetan children and adolescents in high-altitude areas. Our findings are consistent with the conclusions of several studies [ 9 , 14 ]. Compared with girls, the curve relationship of boys is more “steep”, which also shows that the impact of malnutrition and obesity on physical fitness of Tibetan boys is significantly higher than that of girls; especially the impact of BMI on PFI in boys in Lhasa and Nyingchi is more obvious, namely steeper.…”
Section: Discussionsupporting
confidence: 94%
“…For example, a study analyzed the relationship between cardiorespiratory fitness and waist circumference in Chinese children and adolescents; cardiorespiratory fitness was measured by 20 m shuttle run test, and the analysis showed that the relationship between cardiorespiratory fitness and waist circumference showed an inverted “U” curve [ 8 ]. With the deepening of research, in recent years, the use of physical fitness index (PFI), which comprehensively reflects the level of physical fitness, has gradually increased, and the relationship between physical fitness index and health has been deeply analyzed [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These demographics can be helpful in achieving a HRQoL [13,14]. As mentioned above, of the 736 middle-aged women respondents, 312 were having normal BMI (86.4 %), whereas underweight was 4.1% and for overweight was only 9.5%.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the weight of students was measured by a valid scale (SECA 830). BMI and WHR were calculated by standard formulae [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%